Matrix convexity - Ostapenko, V. V. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
The notion of a convex set is generalized. In the definition of ordinary convexity, sums of products of vectors and numbers are used. In the generalization considered in this paper, the role of numbers is played by matrices; this is why we call it “matrix convexity.”